Wars, Cartels and Covid-19: Regime Switching in Commodity Prices - Caputo-Galarce, R; Ordonez-Jofre, F (Routledge, 2024)
Commodity prices are extremely volatile, and volatility itself fluctuates over time. Using data from 1959 to 2022, we estimate a 3-state Markov-switching model to identify expansions and contractions in oil and copper price volatility. We found a transition from a low to a medium variance regime for the oil price, in 1979, reflecting changes in the oil market structure. In addition, we identify infrequent and short-lived episodes of unusually high oil price volatility. For copper, there is no transition across regimes, and episodes of high volatility are not synchronized with the periods of high volatility in oil prices. We found that oil prices are much more volatile than copper prices in all states. Oil prices react more strongly to market cartelization, war episodes, and global demand shifts, like the 2008 Great Recession and the COVID-19. © 2022 Informa UK Limited, trading as Taylor & Francis Group.